O AMBIENTE CONSTRUÍDO PARA HEMODIÁLISE: UMA ANÁLISE DA REVISÃO SISTEMÁTICA DE LITERATURA (RSL) - Bara, Patricia Caetano Gattas; Abdalla, José Gustavo Francis; Oliveira, Juliana Simili de (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Architecture might influence the human experience also in the scope of health buildings, therefore developing an interest for users. The main goal of this paper is the deepening in the knowledge of hemodialysis environments. Methodologically, this is a Literature Systematic Review was developed with planning and focus considers research methods, significant authors and the results. Obtained as conclusion was the lack of studies related to the ergonomics of the dialytic built environment, based on the results found in the portals CAPES, BVS, PUBMED, and ENTAC.